2020
DOI: 10.32358/rpd.2020.v6.446
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Practices of Mozambican Public Employees on the Prevention of Covid-19

Abstract: Objective: To analyze the level of knowledge, attitudes, and practices of Mozambican public employees on the prevention of COVID-19. Methodology/Approach: 126 Mozambican public employees (79 men, 43 women and 4 who chose not to disclose their gender) answered a closed questionnaire applied through the Google Form online platform. The questionnaire was open for 5 days (two weekend and three business days). Findings: The results suggest that employees are knowledgeable; however, efforts should be mad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 5 publications
(9 reference statements)
2
5
0
1
Order By: Relevance
“…It validates that the respondents have adequate knowledge about COVID-19. This result coincides with similar studies in Jordan and abroad [5,[12][13][14][15][17][18][19][24][25][26][27]. The result was expected because the government in Jordan at all levels has released relevant education materials and has delivered COVID-19-related content through various channels, including television, the Internet, and publicity boards.…”
Section: Knowledge About Covid-19supporting
confidence: 88%
See 2 more Smart Citations
“…It validates that the respondents have adequate knowledge about COVID-19. This result coincides with similar studies in Jordan and abroad [5,[12][13][14][15][17][18][19][24][25][26][27]. The result was expected because the government in Jordan at all levels has released relevant education materials and has delivered COVID-19-related content through various channels, including television, the Internet, and publicity boards.…”
Section: Knowledge About Covid-19supporting
confidence: 88%
“…Recent studies on COVID-19 revealed that knowledge [5,9,13] might account for the precautionary actions of the general public. In addition, the results of previous studies revealed that a better level of knowledge is positively associated with the practice of preventive measures [13][14][15][16][17][18], and attitudes also associate positively with preventive behaviors [9,[13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Due to their advantages, CAP studies have been widely used to assess populations' level of knowledge, attitudes, and practices during epidemics. Since the beginning of the COVID-19 pandemic, this research modality has been carried out in several countries ( Akalu et al, 2020 ; Al-Hanawi et al, 2020 ; Austrian et al, 2020 ; Azlan et al, 2020 ; Clements, 2020 ; Erfani et al, 2020 ; Goumenou et al, 2020 ; Hussain et al, 2020 ; Lau et al, 2020 ; Manjate et al, 2020 ; Olapegba et al, 2020 ; Rahman & Sathi, 2020 ; Reuben et al, 2020 ; Rios-González, 2020 ; Zhong et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, web-based inquiry forms become more complex to complete when it comes to open-ended qualitative questions. We believe that in our settings these techniques should be suitable to a limited range of target groups such as professionals, academics or student populations (Manjate et al, 2020).…”
Section: Employment Of Remote Data Collection Approaches During the Cmentioning
confidence: 99%